Intraocular pressure elevation following the use of topical dexamethasone ointment after Squint surgery (2022)
Purpose: To describe the pattern of intraocular pressure (IOP) changes after squint surgery in eyes of black Africans at the University College Hospital, Ibadan, Nigeria. Materials and Methods: This was a retrospective review of the clinical records of patients who underwent squint surgery between 2010 and 2019. Data on demographic characteristics, preoperative and postoperative intraocular pressure values, coexisting ocular pathology, type of strabismus, surgery performed, frequency and duration of postoperative topical steroid use and treatment received for elevated intraocular pressure were collected and descriptively summarised. Results: Thirty-six (39.1%) out of 92 patients who had squint surgery during the study period met study inclusion criteria. Mean age was 20.5 ± 13.6 years. All patients were administered Maxitrol® ointment postoperatively. Baseline, peak and net change in IOP were 12.9 ± 2.6 mmHg, 21.3 ± 6.8 mmHg and 8.39 ± 7.2 mmHg respectively. Thirty-one (86.1%) patients had elevation in IOP from baseline; 21 (67.7%) of these had significant IOP elevation. Topical steroid therapy was tailed off rapidly for all patients with significant IOP elevation. Twelve patients were commenced on topical IOP lowering medications, with normalization of intraocular pressure in majority of them by three months after surgery. Conclusion: Elevated intraocular pressure with the use of topical dexamethasone ointment after squint surgery was common in this study and majority of the patients had significant elevation in intraocular pressure. Close monitoring of the intraocular pressure of black patients, especially children, on topical steroid medication after squint surgery is strongly recommended.